2017
DOI: 10.5483/bmbrep.2017.50.6.039
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell surface markers on normal stem cells

Abstract: The cancer stem cell (CSC) hypothesis has captured the attention of many scientists. It is believed that elimination of CSCs could possibly eradicate the whole cancer. CSC surface markers provide molecular targeted therapies for various cancers, using therapeutic antibodies specific for the CSC surface markers. Various CSC surface markers have been identified and published. Interestingly, most of the markers used to identify CSCs are derived from surface markers present on human embryonic stem cells (hESCs) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
212
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(218 citation statements)
references
References 163 publications
(195 reference statements)
2
212
0
4
Order By: Relevance
“…However, surface epitopes have also created great controversy in the CSC field as some groups have demonstrated tumor initiation for both marker positive and negative populations as well as heterogeneity of marker expression based on microenvironmental factors (Beier et al, ; Shmelkov et al, ). Another issue with cell surface markers is that for every marker identified to date, their expression can also be seen in normal adult stem cells, embryonic stem cells, or normal tissue (Kim & Ryu, ). The presence of surface epitopes can also be inconsistent due to cell cycle‐dependent expression as well as receptor recycling (Jaksch, Munera, Bajpai, Terskikh, & Oshima, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, surface epitopes have also created great controversy in the CSC field as some groups have demonstrated tumor initiation for both marker positive and negative populations as well as heterogeneity of marker expression based on microenvironmental factors (Beier et al, ; Shmelkov et al, ). Another issue with cell surface markers is that for every marker identified to date, their expression can also be seen in normal adult stem cells, embryonic stem cells, or normal tissue (Kim & Ryu, ). The presence of surface epitopes can also be inconsistent due to cell cycle‐dependent expression as well as receptor recycling (Jaksch, Munera, Bajpai, Terskikh, & Oshima, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, CSCs possess characteristics associated with normal stem cells, specifically mulitpotency in the ability to give rise to all cell types found upon pathological examination of an excised tumor [11] . The most commonly used method for identifying and isolating CSCs is via their characteristic cell surface markers, many of which were originally discovered from studies of normal tissue development, including from hematopoiesis and embryonic stem cells and which are also found co-expressed on CSCs [9] .…”
Section: Csc Identification and General Definitionmentioning
confidence: 99%
“…It is only when the CSCs differentiate that they will express greater sets of uniquely characteristic markers for the particular cell lineages that they encompass [11] . It is in this light that the markers for the CR-CSCs are discussed below, and are discussed in reference to related findings of similar markers found expressed on the ESCs and CSCs alike across a range of different cancer types [9,10,12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ITGA6 and ITGB1 are genes of the integrin family, and elevated expression of both genes has been associated with the cSLC phenotype, tissue invasion and capability for metastasis (Brooks et al, 2016;Kim and Ryu, 2017). Vassilopoulos et al (2013) showed in vivo the tumour initiation properties of ITGA6+/ITGB1+/CD24+ cell populations.…”
Section: Disscusionmentioning
confidence: 99%